
Boolean Algebra
Hi
Can anyone expalin to me how
x'y'z' + x'yz' + xyz'
= x'z' + yz'
I can only reach this:
x'y'z' + x'yz' + xyz'
=(y'+y)x'z' + xyz'
=x'z' + xyz'
where do I go next?
Thanks for your time.
EDIT:
Can you repeat an expression from the original equation
i.e. in the equation x'y'z' + x'yz' + xyz' (there are 3 xyz variables)
if I use
x'y'z' + x'yz' = (y+y')x'z' = x'z'
x'yz' + xyz' = (x+x')yz' = yz'
then
result = x'z' + yz'
is this ok?

Yes, the fact that a = a + a is derivable from Boolean algebra axioms (or sometimes is taken as an axiom).